PLC Implementation as a Flow Computer for Calculation of Saturated Steam Mass Meetings with the Linear Divided Regression Method (Application: PT. XYZ - Kuala Tanjung) - Dedy AP; Muhammadi Fitra Zambak; Ahmad AA; Suwarno Suwarno (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2020)
In supporting of production quality improvement, industry must be supported by reliable process system. Reliable measurement system also included in one system which is expected realibility. Specially for saturated steam flow measurement and calculation which is mostly done in the industry in relation to control production cost, should also be able to show accurate results. Now PLC has taken an important role in industry, beside as a control system, PLC also can be used to calculation a formula. This paper aims to use PLC as flow computer to calculate saturatedsteam density by adopting linear regression method which is divided into “n” section to increase the accuration with pressure as a input parameter. The results show a relatively small error value around 0,2% if we compare with standart linear regression method, where the value around 0,9%.